Isolation of solubilizing microorganisms from landfill soil - Siti Nor Amira, Rosli (2017)
characterization and screening of cellulolytic and xylanolytic microorganisms from landfill soil and quantification of their enzymatic activity. Sample was collected from landfill soil of landfill site at Sg. Ikan, Kuala Terengganu, Malaysia. Isolation of the solubilizing microorganism was conducted via standard serial dilution and spread plate method using nutrient agar medium and these microorganisms were further characterized by morphological characteristics and Gram-staining. Screening tests demonstrated the ability of microorganism to produce cellulase and xylanase enzyme via Gram’s iodine-staining. Finally, selected isolates were subjected to enzyme activity quantification such as total cellulase, endoglucanase, exoglucanase and xylanase assay analysis. A total of 58 different isolates were isolated from landfill soil which Gram-positive bacilli were the dominant microorganism. Out of 58 isolates, 29 isolates were selected for further testing. After Gram’s iodine staining, there were 23 cellulolytic microorganisms and 26 xylanolytic microorganisms which showed clear zones on agar plate containing carboxymethyl cellulose and xylan, respectively. Two isolates out of 23 cellulolytic microorganisms and three isolates out of 26 xylanolytic microorganisms with ratio of clear zone (D/d) more than 3.3 were furthered tested for quantification of enzyme activity. Cellulolytic microorganism M12 had the highest endoglucanase activity at 1.7621±0.0054 U/mL while cellulolytic microorganism M28 had the highest total cellulase activity and exoglucanase activity at 1.6086±0.0007 U/mL and 1.8299±0.0704 U/mL, respectively. Meanwhile, xylanolytic microorganism M15 had the highest xylanase activity at 8235±0.1715 U/mL. In conclusion, the 58 microorganisms were isolated which initiated research on industrially important microorganism from landfill soil and these isolates may be vital source for the discovery of industrial useful enzymes especially in municipal solid waste degradation.